2016
DOI: 10.1021/acs.energyfuels.6b00816
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of Arsenic During Coal Combustion Based on Isothermal Thermogravimetric Analysis at 600–1500 °C

Abstract: The volatilization characteristics of arsenic in different coals at 600−1500 °C were studied on an isothermal reaction system. Through thermogravimetric analysis similar to that used for coal analysis, the mass loss and mass loss rate of arsenic for coal samples were determined. Sequential chemical extraction method was used to measure the mode of occurrence of arsenic in the coals. TG-MS techniques were also carried out to study the relationship between sulfur and arsenic. Results show that the volatilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The mixed gas flow rate was maintained at 2.33 L/min throughout the test. Preliminary experiments have verified that the flow rate used eliminate the influence of external diffusion [7,8]. were placed in a corundum boat, and the furnace was quickly pushed along the guide rail to ensure that the coal sample burned in the constant temperature zone of the furnace.…”
Section: Combustion Facilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The mixed gas flow rate was maintained at 2.33 L/min throughout the test. Preliminary experiments have verified that the flow rate used eliminate the influence of external diffusion [7,8]. were placed in a corundum boat, and the furnace was quickly pushed along the guide rail to ensure that the coal sample burned in the constant temperature zone of the furnace.…”
Section: Combustion Facilitymentioning
confidence: 99%
“…The volatilization and partitioning behavior of As is influenced by several factors, including the combustion temperature and combustion atmosphere [7][8][9][10][11]. In O 2 /CO 2 combustion, the CO 2 concentration in the furnace can reach 60%~80% or more [12][13][14][15], which is significantly higher than that in air fired combustion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, the reaction kinetic parameters for the dominant arsenic species, along with the frequency factor and activation energy, were determined through a combination of previous experimental work (through data fitting to establish the vaporization yield model of each arsenic species) [26] and a single-particle combustion model. It is found that the orders of magnitude of the parameters can be obtained with reasonable accuracy allowing for the variations in coal samples and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%